Usability evaluation of activity model through chinese children’s song to enhance culture appreciation - Hailian, Zhang; Ariffin, Azli (EDUCATUM Journal of Social Sciences, 2024)
Preserving cultural heritage is essential to maintain diversity, promote understanding between cultures, and foster a sense of identity and belonging among communities. As a cultural expression, music has been used for centuries to preserve cultural heritage and traditions. Education plays an important role in maintaining a culture even though it is no longer relevant nowadays. Music is an element that is often associated with culture. The purpose of this study is to evaluate the Usability of an Activity Model through Chinese Children’s Song to Enhance Culture Appreciation. This research uses the Fuzzy Delphi Technique (FDM) as a data collection method. The study respondents were 50 randomly selected experts among music educators. The usability evaluation demonstrated the model’s suitability based on five criteria: ease of learning, efficiency, ease of recall, error prevention, and user-friendliness based on the prototype model that had been developed before. These criteria were assessed across element usability, classification, list presentation, relationships, and overall model functionality.